2014
DOI: 10.1039/c4cc07238c
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous exfoliation and tailoring of MoS2in mixed solvents

Abstract: Spontaneous exfoliation of MoS2 is achieved in H2O2-NMP mixed solvents with a yield of over 60 wt%, operated under mild conditions. H2O2-prompted sheet-tailoring effect induces a size evolution of MoS2 nanosheets from micro-scale to nano-scale. Furthermore, the concurrent dissolution also affords an approach to introduce structural defects in the nanosheets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
89
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(100 citation statements)
references
References 33 publications
11
89
0
Order By: Relevance
“…Different concentrations (0.2, 0.4, and 0.6 vol %) of H 2 O 2 solution resulted in the formation of different sizes of the interstitial space in the yolk–shell MoS 2 @C microspheres, denoted as MoS 2 @C‐0.2 %, MoS 2 @C‐0.4 %, and MoS 2 @C‐0.6 %, respectively. The etching mechanism can be described by the chemical reaction given in Equation trueMoS2+90.166667emnormalH2normalO2MoO22++20.166667emSO42-+20.166667emnormalH++80.166667emnormalH2normalO …”
Section: Resultsmentioning
confidence: 99%
“…Different concentrations (0.2, 0.4, and 0.6 vol %) of H 2 O 2 solution resulted in the formation of different sizes of the interstitial space in the yolk–shell MoS 2 @C microspheres, denoted as MoS 2 @C‐0.2 %, MoS 2 @C‐0.4 %, and MoS 2 @C‐0.6 %, respectively. The etching mechanism can be described by the chemical reaction given in Equation trueMoS2+90.166667emnormalH2normalO2MoO22++20.166667emSO42-+20.166667emnormalH++80.166667emnormalH2normalO …”
Section: Resultsmentioning
confidence: 99%
“…The obtained 2D MoS 2 sheets exhibited a lateral dimension of ≈300 nm and a thickness of 1.17 nm. Dong and co‐workers presented the spontaneous exfoliation of MoS 2 powders in H 2 O 2 ‐NMP mixed solvents under mechanical stirring for 10 h . Besides the oxidation effect, H 2 O 2 was reckoned to induce size evolution of MoS 2 nanosheets (single and few layer) from the micro‐ to the nanoscale.…”
Section: Direct Ultrasonic Exfoliation In Liquidmentioning
confidence: 99%
“…Also good wetting capability of solvent is needed for layer surfaces. It is reported that H 2 O 2 can induce the spontaneous exfoliation of MoS 2 in NMP [29]. In detail, 20 mg MoS 2 flakes were dissolved in 20 mL of mixed solvents of Hydrogen Peroxide (H 2 O 2 ) and N-methyl-2-pyrrolidone (NMP).…”
Section: Preparation Of Mos 2 Nanosheetsmentioning
confidence: 99%